Assemblages of native bryophytes in secondary forests with introduced Quercus rubra. (20th September 2016) - Woziwoda, Beata; Staniaszek‐Kik, Monika; Stefańska‐Krzaczek, Ewa
Abstract : We have studied the diversity of bryophytes in planted Polish post‐agricultural forests dominated by the native Scots pine Pinus sylvestris and the alien (North American) red oak Quercus rubra . The planted sites would be suitable for a mesic coniferous forest (abbreviation: CFS) or mesic broadleaved forest (abbreviation: BFS). We analysed the structure and composition of the bryophyte assemblages in relation to forest site and substrate availability. Special attention was paid to the introduced Q. rubra as a host species for native bryophytes. A total of 54 bryophyte species (9 liverworts and 45 mosses) were found in the 90 plots ( = phytosociological relevés, 10 × 10 m in area; 45 at each forest site) studied. DCA analysis showed that the bryophyte assemblages of the P. sylvestris – Q. rubra secondary forest community differed significantly between CFS and BFS sites; the similarity of the composition of bryophyte species was 36.8%. The substrate preferences (epigeic, epixylic, epiphytic), as well as the growth form and life form of the recorded bryophytes, also differed between CFS and BFS, while the proportion of bryophytes that had a particular life strategy was very similar. The introduced Q. rubra was inhabited by 28 bryophyte species, including two liverworts. This tree hosted 64% of the CFS and 47% of BFS bryophyte flora and as a host for epiphytes the species successfully fulfilled the functional role of the native oaks ( Q. robur and Q. petraea ). Thus, the introduction of Q. rubra may contribute to the restoration of post‐agricultural forests and to the conservation of epiphytic bryophyte species. On the other hand, the negative impact of Q. rubra observed on the ground flora (including bryophytes) puts the benefits of Q. rubra for the conservation of native biodiversity in general in question.